Surgical excision of sebaceous nevus in children: What are the risks? - Man Yee Paula Tang; Sih Yin Nicholas Chao (Wolters Kluwer Medknow Publications, 2019)
Background: Sebaceous naevus is a common dermatological condition seen in children. Evidence on the incidence and prevalence of the complication of surgical excision is lacking. Objectives: We aim to review our single center's experience in managing paediatric patients with sebaceous naevus in the past ten years. Methods: We retrospectively reviewed the clinical records of patients with surgical excision of sebaceous naevus performed in our center in the past ten years. Results: 70 surgical excisions of sebaceous naevus were reviewed. 13% were planned staged excision while 5.7% were unplanned revisional excision. 84% of the excision were performed under general anaesthesia and 4.2% were performed under local anaesthetics. Conclusion: A complication rate of 5.7% for unplanned second operation was noted for paediatric patients undergoing sebaceous naevus excision.